Demonstration and solubilization of antigens expressed primarily on the surfaces of Candida albicans germ tubes. - Smail, E H (1984)
Antisera against mycelial-phase, but not yeast-phase, Candida albicans absorbed with yeast-phase organisms preferentially stained germ tube segments of several strains of mycelial-phase C. albicans by the indirect fluorescent-antibody staining technique. Germ tube segment antigens were not found in significant amounts on blastospore segments or on yeast-phase organisms. Absorption of the mycelial-phase reference sera with yeast-phase C. stellatoidea, but not with C. tropicalis, C. guillermondii, or Saccharomyces cerevisiae, resulted in preferential germ tube segment staining of C. albicans. A dithiothreitol extract of mycelial-phase C. albicans organisms blocked staining of the germ tube segment, but a dithiothreitol extract of yeast-phase organisms did not. When dithiothreitol extracts from both phases were reacted against yeast-absorbed reference sera in tandem crossed and crossed line immunoelectrophoresis, a cross-reacting arc and several arcs unique to the mycelial-phase extract were noted. Immunofluorescent staining tests were performed, using appropriately absorbed sera from patients with candidiasis to stain a laboratory strain of C. albicans. Human tissue slices infected with C. albicans were used as targets for appropriately absorbed rabbit antisera. These human data indicated that antigens preferentially expressed on the germ tube in vitro were also expressed on filamentous structures of the fungus in infected human tissues. In vitro and in vivo, the invasive mycelial phase of C. albicans expresses certain antigens that are highly concentrated on the germ tube.